Rhizobium spp. Populations and mycorrhizal associations in some plantations of forest tree species - Bonetti, Roberto; Oliveira, Luiz A.; Magalhães, Fátima M.M. (Pesquisa Agropecuaria Brasileira, 2014)
The occurrence of nodulation and mycorrhizal association in several forest tree plantations at reserva Ducke/INPA (km 25 M 010-AM-Brazil) was investigated. The species of indigenous forest trees studied were: Cedrelinga catenaeformis (cedroana), Calophyllum brasiliense (jacareuba), Dipterix odorata (cumaru), Carapa guianensis (andiroba), Dipterix potiphylla (cumarurama), Goupia glabra (cupiúba), Tabebuia serratifolia (pau d'arco), Clarisía racemosa (Guariúba-folha-fina), Pithecellobium racemosum (angelim-rajado), Vouacapoua pallidior (acapu), Eperua bijuga (muirapiranga) and Diplotropis sp. (sucupira). The only leguminous trees that showed nodules were C. catenaeformis and V. pallidior on clay and sandy soil respectively. The lack of nodulation was not correlated with Rhizobium populations. The amount of V.A. mycorrhizal spores in the soil were not seen to be correlated with root infection. All tree species showed V.A. mycorrhizal infection, and one of the higher infection in C. catenaeformis.
Keywords: legume trees; nodulation; nitrogen fixation